Natural ageing primarily affects the initial response to a sustained walking perturbation but not the ability to adapt over time - Swart, S. B.; den Otter, A. R.; Lamoth, C. J. C. (Frontiers in Physiology, 2023)
The ability to flexibly respond and adapt the walking pattern over time to unexpected gait perturbations is pivotal for safe and efficient locomotion. However, these abilities might be affected by age due to age-related changes in sensorimotor functioning. In this cross-sectional lifespan study, we used a split-belt paradigm to determine how age affects the initial response (i.e., flexibility)—and the ability to adapt after prolonged exposure—to a sustained gait perturbation. Healthy adults (N=75) of different ages (12–13 per decade) were included and walked on a split-belt treadmill, in which a sustained gait perturbation was imposed by increasing one of the belt speeds. Linear regression models, with the evoked spatiotemporal gait asymmetry during the early perturbation and late adaptation, were performed to determine the effects of age on the flexibility and adaptability to split-belt walking. Results showed that the flexibility to respond to an unexpected perturbation decreased across the lifespan, as evidenced by a greater step length asymmetry (SLA) during the early perturbation phase. Despite this reduced flexibility in step lengths, late adaptation levels in SLA were comparable across different ages. With increasing age, however, subjects needed more steps to reach a stable level in SLA. Finally, when the belts were set to symmetrical speeds again, the magnitude of SLA (i.e., the aftereffects) increased with age. Collectively, these findings suggest that natural ageing comes with a decrease in gait flexibility, while the ability to adapt to split-belt walking was not affected by age—only how adaptation was achieved.